2019
DOI: 10.15520/jcmro.v2i11.226
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor and Outcome of Retinopathy of Prematurity among Premature Babies admitted to Tertiary Care Hospital: A Retrospective Observational Study

Abstract: Background: Retinopathy of Prematurity (ROP) is a multifactorial vasoproliferative retinal disorder that increases in incidence with gestational age. ROP is a vascular retinal disease that can cause low vision or blindness. ROP is a common blinding disease in children which is becoming increasingly prevalent in the developing world. Aim: The aim of this study is to evaluate the incidence of Retinopathy of prematurity (ROP) and its association with risk factors such as low birth weight, gestational age, oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…10 In another study by Paranjpe et al from Maharashtra, the reported incidence of ROP was 35.62%. 11 A similar incidence with a slightly higher incidence has been reported in other studies ( Table 5 ). 12–19 The mean BW of screened babies was 1538.11gm range (580–3500), and the mean GA was 31.89 weeks range (26–39) weeks.…”
Section: Discussionsupporting
confidence: 89%
“…10 In another study by Paranjpe et al from Maharashtra, the reported incidence of ROP was 35.62%. 11 A similar incidence with a slightly higher incidence has been reported in other studies ( Table 5 ). 12–19 The mean BW of screened babies was 1538.11gm range (580–3500), and the mean GA was 31.89 weeks range (26–39) weeks.…”
Section: Discussionsupporting
confidence: 89%